Performance of a refurbished unmanned combat air vehicle model with trailing edge blowing - Khalid, Mahmood (Journal of King Abdulaziz University: Engineering Sciences, 2023)
A CAD Unmanned Combat Air Vehicle (UCAV 1303) model is constructed from the surface geometry information gleaned from different publications. A simple C- grid is constructed for the purpose of studying the effect of a sheet of ejection jet installed at the thicker portion of the trailing edge to investigate possible effects it could have upon the aerodynamic lift and drag of the UCAV 1303 model. The blowing seemed to improve the lift and make a marginal improvement upon drag.